العلاقات الدولية في ظل الاتفاقيات الليبية الإيطالية‎‏ في مجال ‏الصحة والاقتصاد : دراسة تحليلية‎ ‎من سنة ‏‏1951م إلى 2018م - أبو رويص، عبد الفتاح الهادي أبو بكر
This study aimed to identify the agreements signed between the Libyan and Italian ‎governments in the economic, health and emigration aspects, with a major focus on ‎the Benghazi Agreement. The study concluded that these treaties include a number of ‎positive aspects of the two parties. They contributed to creating a climate conducive ‎to improvement. Great in bilateral relations. But most of the terms of the Italian ‎agreements concluded with the Libyan side remained a dead letter because of the ‎security chaos and conflicts inside Libya after the February 2011 revolution prevents ‎the achievement of any prior agreement. The study also showed that the Italian-‎Libyan relationship is a historical relationship that embodied the worst forms of ‎exploitation and colonialism. The Treaty of Friendship, Partnership and Cooperation ‎of Italy and Libya (Benghazi Treaty) signed by the center-right government led by ‎‎"Silvio Berlusconi" with Colonel "Gaddafi", Under this agreement, Italy promised to ‎grant 30 billion dollars to Libya, in addition to the first official and frank apology ‎from any European country for colonialism. The main reason for Libya's preferential ‎treatment is due to: The strategic importance of Libyan oil and the size of huge ‎reserves of about forty-nine billion barrels and a daily production of 2.3 million ‎barrels per day‏.‏‎ Italy is looking to attract Libyan investments, especially the large ‎size of the investment of the Libyan sovereign fund‏.‏‎ ‎‏ ‏Its location as a transit country ‎for migrants attempting to enter Europe through Italy‏.‏‎ The sharp character of Gaddafi ‎and his insistence on an Italian apology, especially with regard to the damage caused ‎by colonialism, and his friendship with Silvio Berlusconi certainly contributed to ‎weaving the threads of that unique relationship. This study followed the historical ‎methodology along with the analytical approach, and reached conclusions and ‎recommendations highlighted at the end of the research.